Identification of Schistosoma mansoni miracidia attractant candidates in infected Biomphalaria glabrata using behaviour-guided comparative proteomics - Fogarty, Conor E.; Phan, Phong; Duke, Mary G.; McManus, Donald P.; Wyeth, Russell C.; Cummins, Scott F.; Wang, Tianfang (Frontiers in immunology, 2022)
Schistosomiasis, caused by infection with Schistosoma digenetic trematodes, is one of the deadliest neglected tropical diseases in the world. The Schistosoma lifecycle involves the miracidial infection of an intermediate freshwater snail host, such as Biomphalaria glabrata . Dispersing snail host-derived Schistosoma miracidia attractants has been considered a method of minimising intermediate host infections and, by extension, human schistosomiasis. The attractiveness of B. glabrata to miracidia is known to be reduced following infection; however, the relationship between duration of infection and attractiveness is unclear. Excretory-secretory proteins (ESPs) most abundant in attractive snail conditioned water (SCW) are key candidates to function as miracidia attractants. This study analysed SCW from B. glabrata that were naïve (uninfected) and at different time-points post-miracidia exposure (PME; 16h, 1-week, 2-weeks and 3-weeks PME) to identify candidate ESPs mediating Schistosoma mansoni miracidia behaviour change, including aggregation and chemoklinokinesis behaviour (random motion, including slowdown and increased turning rate and magnitude). Miracidia behaviour change was only observed post-addition of naïve and 3W-PME SCW, with other treatments inducing significantly weaker behaviour changes. Therefore, ESPs were considered attractant candidates if they were shared between naïve and 3W-PME SCW (or exclusive to the former), contained a predicted N-terminal signal peptide and displayed low identity (<50%) to known proteins outside of the Biomphalaria genus. Using these criteria, a total of 6 ESP attractant candidates were identified, including acetylcholine binding protein-like proteins and uncharacterised proteins. Tissue-specific RNA-seq analysis of the genes encoding these 6 ESPs indicated relatively high gene expression within various B. glabrata tissues, including the foot, mantle and kidney. Acetylcholine binding protein-like proteins were highly promising due to their high abundance in naïve and 3W-PME SCW, high specificity to B. glabrata and high expression in the ovotestis, from which attractants have been previously identified. In summary, this study used proteomics, guided by behavioural assays, to identify miracidia attractant candidates that should be further investigated as potential biocontrols to disrupt miracidia infection and minimise schistosomiasis.